Consistency of the Non-Invasive Monitoring Preemie Car Seat (PreeCASE) Device in Assessing Heart Rate, SpO2 Level, and Body Temperature of the Infants - Muhammad Afiq Firdaus, Md Zin; Mohd Azrul Hisham, Mohd Adib (Universiti Malaysia Pahang, 2024)
Advancements in technology have made pulse oximeter devices the preferred choice for parents monitoring their baby's health. However, existing devices present challenges for infants, especially preemies, who need continuous monitoring after being discharged from the hospital. Using conventional baby car seats with wired connections and unstable external vital sign monitors may lead to inaccurate data readings. To resolve this issue, the non-invasive monitoring preemie car seat (PreeCASE) device is well-developed. In this study, we focus on investigating the consistency of the PreeCASE device in assessing the heart rate, SpO2 level, and body temperature of healthy infants. For the methods, ten healthy infants are selected to use the PreeCASE device, and the data is collected and analyzed using standard procedure. The PreeCASE device provides consistent data readings for the three main physiological parameters, heart rate SpO2 level, and body temperature that are displayed on an LCD screen based on the user’s respective levels. The PreeCASE device is precisely designed to facilitate easy and rapid monitoring of infants, especially preemie infants. This innovative device holds significant potential to improve and support pediatricians in effectively caring for infants in Malaysia.